Elevation‐induced climate change as a dominant factor causing the late Miocene C_4 plant expansion in the Himalayan foreland - Wu, Haibin; Guo, Zhengtang; Guiot, Joël; Hatté, Christine; Peng, Changhui; Yu, Yanyan; Ge, Junyi; Li, Qin; Sun, Aizhi; Zhao, Deai (Global Change Biology, 2014)
Abstract During the late Miocene, a dramatic global expansion of C 4 plant distribution occurred with broad spatial and temporal variations. Although the event is well documented, whether subsequent expansions were caused by a decreased atmospheric CO 2 concentration or climate change is a contentious issue. In this study, we used an improved inverse vegetation modeling approach that accounts for the physiological responses of C 3 and C 4 plants to quantitatively reconstruct the paleoclimate in the Siwalik of Nepal based on pollen and carbon isotope data. We also studied the sensitivity of the C 3 and C 4 plants to changes in the climate and the atmospheric CO 2 concentration. We suggest that the expansion of the C 4 plant distribution during the late Miocene may have been primarily triggered by regional aridification and temperature increases. The expansion was unlikely caused by reduced CO 2 levels alone. Our findings suggest that this abrupt ecological shift mainly resulted from climate changes related to the decreased elevation of the Himalayan foreland.